Pengaruh Budaya Organisasi, Komitmen dan Motivasi Kerja terhadap Kinerja Karyawan: - Made Sefka Lesmana; Kusuma Candra Kirana; E Didik Subiyanto (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study examines the influence of organizational culture, commitment, and work motivation on employee performance. The purpose of this study was to determine the effect (simultaneously or partially) of organizational culture, commitment, and motivation on employee performance. The location of this research was at UPH Maju Mapan, Gunung Kidul with a total sample of 50 respondents, namely all employees at UPH Maju Mapan. The method used in this study is a quantitative method with primary data obtained through questionnaires. The results of the study were (1) UPH Maju Mapan employees in Gunung Kidul had an organizational culture in the good category, a work commitment culture in the good category, and work motivation in the good category. (2) Organizational culture, commitment, and motivation have a significant influence (both partially and simultaneously) on employee performance. (3) Organizational culture, commitment, and motivation have an influence of 75.8% on the performance of employees at UPH Maju Mapan Gunung Kidul, the remaining 24.2% is influenced by other variables outside the research. Keywords: organizational culture, commitment, work motivation, employee performance